Предмет:
АлгебраАвтор:
brandiv82iАвтор:
kaylaАвтор:
beautyjiz7Автор:
pixie stickr2iw1) (a-b)(a+b)(a^2+b^2)=
(a^2-b^2)(a^2+b^2)=
a^4-b^4
a^4-b^4=a^4-b^4
2) (a^4+b^4)(a^2+b^2)(a-b)(a+b)=
(a^4+b^4)(a^2+b^2)(a^2-b^2)=
(a^4+b^4)(a^4-b^4)=
a^8-b^8
a^8-b^8=a^8-b^8
Автор:
mia36Добавить свой ответ
Предмет:
Английский языкАвтор:
twiggy13nnОтветов:
Смотреть
Предмет:
ИсторияАвтор:
mckenzie57Ответов:
Смотреть
Предмет:
АлгебраАвтор:
candiceopvxОтветов:
Смотреть
Предмет:
Қазақ тiлiАвтор:
baby makergkygОтветов:
Смотреть